Entrepreneurial Leaders and the Dissemination of Entrepreneurial Orientation - Barreto, João Carlos; Nassif, Vânia Maria Jorge (Review of Business Management, 2014)
The objective of this research is to analyze whether entrepreneurs’ leadership behaviors in small and micro enterprises that provide services contribute to the dissemination of the many dimensions of entrepreneurial orientation. This is basic qualitative research of an exploratory and interpretative nature, carried out by means of interviews – with a semi-structured script – applied to five entrepreneurs who are MSE leaders. Research data was analyzed through content analysis proposed by Bardin (2008), and narratives, according to Gibbs (2009). The results reveal that entrepreneurs use the dimensions of entrepreneurial orientation with varying intensity and in an informal way, because they are not familiar with the practices of these dimensions.